L’espace social des étudiants marocains dans la mobilité internationale. Spatialisation des réseaux et recomposition territoriale - Sabrina Marchandise (Netcom)
This paper deals with international student migration, particulary on Moroccan students. This issue appears in a context of internationalization of higher education and knowledge and skills mobility. The overall objective of the research lies in understanding how Moroccan students represent, design and produce their relationship to space, territorializing many areas. How then to think of Moroccan students’ new forms of territoriality? Spatial translations of the various factors involved in the students’ social dynamics can provide the keys to reading and interpretating current changes (practices and technologies). The project aims at understanding how the structure of social space is for students across different networks. This will be achieved through the network spatialisation of Moroccan students.